AI-POWERED POLITICAL CAMPAIGNS: ETHICAL IMPLICATIONS AND REGULATORY CHALLENGES - S Narayana (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The integration of Artificial Intelligence (AI) into political campaigns has reshaped the democratic landscape across the world. AI-driven technologies such as data analytics, predictive modelling, chatbots, and automated content generation have transformed how political parties engage with voters, manage public opinion, and strategize electoral activities. While these innovations have enhanced campaign efficiency, improved voter outreach, and allowed for targeted communication, they have simultaneously raised complex ethical and regulatory questions that remain largely unresolved. One of the foremost ethical concerns is the invasion of voter privacy. AI tools often rely on large-scale data harvesting, sometimes without adequate consent, leading to the creation of detailed voter profiles that can be exploited for micro-targeting and psychological manipulation. Moreover, AI-fueled misinformation campaigns, including deepfakes and automated bots, threaten to distort public discourse and erode trust in democratic institutions. These risks are compounded by the opaque nature of AI systems, which makes accountability and transparency difficult to ensure. On the regulatory front, most countries lack comprehensive legal frameworks to govern the use of AI in political campaigns. Existing data protection laws are often inadequate to address the rapid evolution of AI technologies and their application in the political domain. The absence of strict guidelines allows political entities to leverage AI in ways that may compromise electoral fairness and manipulate voter choices without facing legal repercussions. This paper critically examines the intersection of AI and political campaigns, focusing on the ethical dilemmas and regulatory gaps that accompany this technological shift. It highlights global and national case studies to illustrate these challenges and proposes potential policy interventions aimed at ensuring that AI serves as a tool to strengthen, rather than undermine, democratic processes.